Misconceptions about HIV infection faced by diagnosed Ghanaian women - MWINI-NYALEDZIGBOR, P.P.; WRIGHT, S.C.D. (African Journal of Midwifery and Women’s Health, 2011)
Background: This paper reports on the expressions of people’s misconceptions about women infected with HIV and AIDS Majority of people living with HIV and AIDS in sub-Saharan Africa are women with the proportion of women continually increasing, constituting 61% while the global percentage of women living with HIV and AIDS is stable at 50% (UNAIDS, 2007). In Ghana, females are four times more at risk of contracting HIV than males (National AIDS/Sexually Transmitted Infections Control Programme, 2010). Meanwhile, available literature show that various misconceptions exist among Africans that HIV and AIDS is a disease of the female prostitute. Women are considered guilty of spreading HIV and other sexually transmitted infections (Quan-Baffour, 2007). Purpose of the study: The purpose of the study was to explore how HIV-positive women receiving care from an NGO-based support framework expressed the misconceptions people have regarding their HIV diagnosis. Methods and sample: A qualitative, explorative and contextual research design was used. The sampling method was purposive and convenience. Self-reported data were gathered using semi-structured interviews. Tesch in Creswell, (2009) hermeneutical analysis approach was used to analyze the data. Sampling was based on data saturation and totaled 16 (n=16). Results: The main theme was ignorance with sub themes emerging from the data-the sub themes included; AIDS is prostitutes’ disease, HIV-infection is punishment from God, HIV/AIDS is a spoiled woman’s disease (Muora) and HIV-positive woman can transmit the virus to people by sitting on the chair she used, touching her hand or big toe or crossing her urine. Conclusion: Misconceptions and beliefs about the mode of transmission of HIV is a social phenomenon that works against controlling the spread of the epidemic. Fear and awe are engendered in people about the disease. With knowledge about the mode of transmission, society will be in a better position to put in place measures to deal with the epidemic.
Keywords: HIV-infection; misconceptions; myths; women; Ghana